Pemanfaatan Limbah Rambut Manusia dan Limbah Karbit Sebagai Substitusi Plafond - Ramadhani, Putri Karisma; Karuniawan, Muh.Fauzi Alfani; Fauziyah, Shifa; H, Hartono (Universitas Diponegoro, 2023)
Ceiling or what is often called the ceiling is a non-structural component in a building. GRC (Glasfiber Reinforced Cement) ceiling is composed of components of sand, cement, water, fiberglass. It contains the same ingredients as fiberglass and human hair, namely calcium, iron and silica. Similar to human hair waste, there has not been much innovation in utilizing carbide waste. Carbide waste contains CaO which is a basic ingredient in cement manufacture. In this study using the experimental method. The purpose of this study was to determine the flexural strength and compressive strength of the ceiling. In this study, 4 samples were used with a differentiating concentration of 5% each, including: F0: 0 %, F1: 10%, F2: 15%, F3: 20 %. Tests in this study included density, water absorption, and flexural strength tests. The results of the characterization of the ceiling grc produced in the physical properties test: density resulted in values of 1.97 gr/cm3, 2.17 gr/cm3, 2.11 gr/cm3, 1.98 gr/cm3, sample F1 the percentage of hair fiber was 10% the highest density compared to other samples. Based on the results of the density test, it is classified as PSKT (High Density Fiber Board) with a density value of ˃ 0.84 gr/cm3. The results of the water absorption values based on the tests include: F0 of 10.78%, sample F1 of 10.24%, sample F2 of 10.43%, and sample F3 of 10.92%, according to the water absorption test that has been carried out, the formula the best was found in sample F1 with the least water absorption with a 10% hair fiber percentage of 10.24%. The results of the density test with water absorption are inversely proportional. While the mechanical properties test: flexural strength in F0 was 34261.92 kgf/cm², sample F1 was 37321.02 kgf/cm², sample F2 was 38544.66 kgf/cm², and the highest sample was in F3 with a percentage of hair fiber of (20 %) of 39768.3 kgf/cm².